The relationship of pathologies of the oral mucosa and gastrointestinal tract in patients with diagnoses of depressive episode and recurrent depressive disorder. Clinical features of dental status (LLC "Endo Press", 2020)
The article presents an overview of the literature on the causes of mood disorders and their impact on the nature and severity of pathological processes in the oral cavity. 25 patients with diagnoses of depressive episode and recurrent depressive disorder between the ages of 20 and 60 were examined. The control group consisted of 15 apparently healthy individuals of similar age and sex who applied to the dental office to dental health. The common methods of dental examination were used. The complaints, the duration of symptoms, frequency of treatment to the dentist, the nature of personal oral hygiene were investigated. It was found that the main factors affecting the intensity of caries, its complications and periodontal disease in the patients examined were the duration and severity of psychopathology